2022
DOI: 10.3389/fchem.2022.874685
|View full text |Cite
|
Sign up to set email alerts
|

Study of Relaxations in Epoxy/Rubber Composites by Thermally Stimulated Depolarization Current and Dielectric Spectroscopy

Abstract: Liquid rubber toughened epoxy resins are widely used in electrical equipment and electronic packaging. Previous studies have only investigated the relaxation process of epoxy resins through dielectric spectroscopy. The trap characteristics of the relaxation process by thermally stimulated depolarization current (TSDC) analysis are less studied. In this work, TSDC and broadband dielectric spectroscopy techniques were used to complementarily characterize the dielectric relaxation process of hydroxyl-terminated l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 30 publications
(41 reference statements)
0
1
0
Order By: Relevance
“…H. Zhang et al have reported the evolution of space charge behaviors for epoxy resins with a 24 h electric field load, and the results show the space charge accumulation cannot meet a stable state within 24 h at a temperature below 60 °C, which suggests that a long-term space charge evaluation is necessary for the insulation of HVDC or UHVDC power equipment (Zhang et al, 2022). C. Wang et al have studied the trap characteristics for specific liquid rubber toughened epoxy resins through the thermally stimulated depolarization current method, finding that the trap energy level increases with an increasing rubber concentration, which may be considered in the application in such an epoxy resin system (Wang et al, 2022). C. Chen et al have investigated space charge accumulation for the SiC-epoxy resin interface, which may affect the insulation reliability of packaging materials (Chen et al, 2022).…”
mentioning
confidence: 99%
“…H. Zhang et al have reported the evolution of space charge behaviors for epoxy resins with a 24 h electric field load, and the results show the space charge accumulation cannot meet a stable state within 24 h at a temperature below 60 °C, which suggests that a long-term space charge evaluation is necessary for the insulation of HVDC or UHVDC power equipment (Zhang et al, 2022). C. Wang et al have studied the trap characteristics for specific liquid rubber toughened epoxy resins through the thermally stimulated depolarization current method, finding that the trap energy level increases with an increasing rubber concentration, which may be considered in the application in such an epoxy resin system (Wang et al, 2022). C. Chen et al have investigated space charge accumulation for the SiC-epoxy resin interface, which may affect the insulation reliability of packaging materials (Chen et al, 2022).…”
mentioning
confidence: 99%